Profil Kematian Neonatal di Rumah Sakit Umum Daerah dr. M. Haulussy Regional Hospital, Indonesia: Hasil Penelitian - Marischa Tita Thiono; Masayu Ramadhani Polanunu (Cermin Dunia Kedokteran, 2025)
Background: The infant mortality rate (IMR) is one of the indicators commonly used to determine overall public welfare. This study aims to look deeper into the profile of neonatal mortality in Maluku region, particularly at dr. M. Haulussy Regional Hospital. Methods: This study was conducted on the neonatal population in the neonatal intensive care unit (NICU) of dr. M.Haulussy Regional Hospital DR M Haulussy from January 1, 2022, to August 31, 2023. A total of 34 neonates met the inclusion criteria. Results: The main factors causing neonatal death were respiratory failure/asphyxia, LBW, and sepsis with the percentage of 25.6%, 24.4%, and 22.2% respectively. Conclusion: The most common factors of neonatal mortality in this sample population were respiratory failure/asphyxia, LBW/BBLR/BBLT, and sepsis.